Development of a mine closure and sustainable transitions micro-credential - challenges and perspectives - Barakos, George; Tapia Rivera, R.; Wightman, E. (AusIMM, 2024)
The continuously growing demand for critical minerals translates to finding and exploiting new mineral resources, meaning numerous new mining projects are expected to initiate operations. Accordingly, these operations must be properly closed and rehabilitated when production ends. Mine closure and post-mining transition are critical stages in a mining operation’s life cycle. Such processes involve the planned and systematic measures to conclude mining activities and restore the affected area to an environmentally sustainable condition. Transforming mining economies to enable communities and other stakeholders to build a successful post-mine future is a constantly growing challenge. As mining matures worldwide, the need for professionals with the skills to engage with the many dimensions and impacts of mine closure is accelerating. Closure practitioners typically move from other parts of the mining industry. Hence, there is an urgent need to create resources that provide essential knowledge in this field. Training professionals in mine closure and post-mining transition is essential to address closure’s environmental, social, legal, and financial aspects effectively. This educational gap has attracted the interest of stakeholders worldwide, who have initiated research projects, workshops, webinars, and online resources. Accordingly, the University of Queensland (UQ) and Curtin University (CU) have partnered with CRC TiME to develop the first Massive Open Online Course (MOOC) entitled ‘The Foundations of Mine Closure and Sustainable Transitions.’ This project aims to build the workforce’s capacity to engage with and deliver effective mine closure and post-mining transitions and formalise professional skills development. A pilot course was launched in October 2023 with 407 participants from 33 countries. In this work, we discuss the challenges during development, the feedback received, and the future perspectives of this foundational course that will enable an element of standardisation in training those involved from the multiple perspectives of those impacted by mine closure.